Cu-catalyzed cross-coupling of methyl ketones and pyridin-2-amines for the synthesis of N-(2-pyridyl)-α-ketoamides. Issue 5 (May 2021) - Chen, Ali; Yang, Daji; Yu, Yue; Liu, Xiang; Rao, Chuixiong; Lin, Haoming; Guo, Pengfeng
An efficient copper-catalyzed strategy for the synthesis of α-ketoamides via cross-coupling of methyl ketones and pyridin-2-amines is described. This transformation has provided a simple process for the formation of C−N and C=O bonds to prepare α-ketoamides, which are important substrates and intermediates for the preparation of fine chemicals. The reaction mechanism is investigated, which suggests that the reaction proceeds via a radical pathway.